Detained In the Scare. Resistance Practices on The Border-Territory - Alvarado, Mariana; Fischetti, Natalia (Millcayac - Revista Digital de Ciencias Sociales, 2025)
This paper assumes and shares previous inquiries that organize and systematize the feminisms of the South to enter, in a partial and fragmented way, into their ancestral knowledge weavings. From Gloria Anzaldúa and Moira Millán it goes through Luz en lo oscuro (2021) and Terricidio (2024) to weave a spiritual activism as a practice of resistance to patriarchy, colonialism, capitalism and speciesist anthropocentrism. In it we rehearse a healing reading practice to rewrite and conjure the scare in the border-territory we inhabit.